Three-component nanorotors generated from fusion of complexes and post-fusion metal–metal exchange. Issue 37 (25th April 2017) - Goswami, Abir; Paul, Indrajit; Schmittel, Michael
Abstract : The fusion of two homoleptic complexes quantitatively created a novel three-component nanorotor. Abstract : The fusion of two homoleptic complexes quantitatively created a novel three-component nanorotor. The intra-supramolecular rotational dynamics leads to a rapid exchange ( k 298 = 24.0 ± 2.5 kHz) of two degenerate Npy → ZnPor interactions. Metal exchange at the remote HETTAP complexation site provided a faster nanorotor ( k 298 = 34.0 ± 3.0 kHz).